Microleakage Evaluation at Implant-Abutment Interface Using Radiotracer Technique - Hakimeh Siadat; Mahnaz Arshad; Hossein-Ali Mahgoli; Babak Fallahi (Tehran University of Medical Sciences, 2016)
Objectives: Microbial leakage through the implant-abutment (I-A) interface results in bacterial colonization in two-piece implants. The aim of this study was to compare microleakage rates in three types of Replace abutments namely Snappy, GoldAdapt, and customized ceramic using radiotracing. Materials and Methods: Three groups, one for each abutment type, of five implants and one positive and one negative control were considered (a total of 17 regular body implants). A torque of 35 N/cm was applied to the abutments. The samples were immersed in thallium 201 radioisotope solution for 24 hours to let the radiotracers leak through the I-A interface. Then, gamma photons received from the radiotracers were counted using a gamma counter device. In the next phase, cyclic fatigue loading process was applied followed by the same steps of immersion in the radioactive solution and photon counting. Results: Rate of microleakage significantly increased (P≤0.05) in all three types of abutments (i.e. Snappy, GoldAdapt, and ceramic) after cyclic loading. No statistically significant differences were observed between abutment types after cyclic loading. Conclusions: Microleakage significantly increases after cyclic loading in all three Replace abutments (GoldAdapt, Snappy, ceramic). Lowest microleakage before and after cyclic loading was observed in GoldAdapt followed by Snappy and ceramic.